2019
DOI: 10.1088/1674-1056/28/7/076106
|View full text |Cite
|
Sign up to set email alerts
|

Impact of proton-induced alteration of carrier lifetime on single-event transient in SiGe heterojunction bipolar transistor*

Abstract: This paper presents an investigation into the impact of proton-induced alteration of carrier lifetime on the single-event transient (SET) caused by heavy ions in silicon–germanium heterojunction bipolar transistor (SiGe HBT). The ion-induced current transients and integrated charge collections under different proton fluences are obtained based on technology computer-aided design (TCAD) simulation. The results indicate that the impact of carrier lifetime alteration is determined by the dominating charge collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…3(1a), 3(2a), and 3(3a) or 3(1b), 3(2b), and 3(3b) shows that the most pronounced potential collapse is produced by incidence from the centre of the emitter under the same bias conditions. SETs generated by the incidence of various secondary particles are obtained [16,17] as shown in Figs. 4.…”
Section: Setting Of Experimental Conditionsmentioning
confidence: 99%
“…3(1a), 3(2a), and 3(3a) or 3(1b), 3(2b), and 3(3b) shows that the most pronounced potential collapse is produced by incidence from the centre of the emitter under the same bias conditions. SETs generated by the incidence of various secondary particles are obtained [16,17] as shown in Figs. 4.…”
Section: Setting Of Experimental Conditionsmentioning
confidence: 99%
“…At each sensitive point, the transient current and charge collection of each sensitive point were tested with an oscilloscope under different bias voltages. [12] To ensure the effectiveness of the experiment, the device was in the worst bias state. Since the SiGe HBT substrate does not directly lead out the electrode, the values of V E = V B = 0 were always maintained, and V C was connected to a positive voltage.…”
Section: Setting Of Experimental Conditionsmentioning
confidence: 99%
“…From the transient current peak value and the amount of charge collected it can be concluded that with an increase in laser incident energy, the collector transient current peak value, the transient current duration and the amount of charge collected amount also gradually increased. [12,22] -110 -90 -70 -50 -30 -10…”
Section: Impact Of the Bias Voltage And Laser Energy On The Single Ev...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, for the SiGe HBTs with DTI around the intrinsic device (i.e. the emitter-base-collector stack), the sensitive volume is determined by the deep trench, [11,16,28,29] which leads to an aspect ratio much smaller. Therefore, the impact of proton incident angle may vary among different SiGe technologies and should be carefully considered in the SET ground testings.…”
Section: Angular Distribution Of Proton-induced Secondary Particlesmentioning
confidence: 99%